Analysis of Financial Statements As A Means of Measuring Financial Performance In The Banking Business In Indonesia - Wirda Azzahra; Amanda Wulandari; Najla Harianto; Tia Sucipto (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
This study aims to analyze financial statements as a tool for measuring financial performance in the banking business in Indonesia. Financial statements are essential sources of information for assessing the health and stability of banks and supporting effective strategic decision-making. The analysis of financial statements is conducted using ratio analysis methods, including liquidity, solvency, and profitability ratios, each of which provides insights into a bank’s ability to meet short-term and long-term obligations, as well as generate profits. This research uses secondary data, including annual financial statements and literature studies, to evaluate the financial performance of banks in Indonesia. The findings show that financial statements, especially through ratio analysis, are highly useful for measuring financial performance and providing a comprehensive picture of the efficiency and effectiveness of bank financial management. These findings can serve as a reference for bank management in formulating better financial policies and for stakeholders to evaluate potential risks and investment opportunities in the banking sector.